The capability approach and the sustainable development goals : inter/multi/trans disciplinary perspectives - Ikejiaku, Brian-Vincent (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This book demonstrates how the capability approach to human development can contribute to the realisation of the 2015 United Nations Sustainable Development Goals (SDGs). The capability approach dictates that success should not be measured by economic indicators, but by people leading meaningful, free, fulfilled, happy or satisfied lives. Drawing from a range of disciplinary perspectives, this book argues that it is vital that the focus for the SDGs should shift to benefiting the most vulnerable. Case studies from across Asia, Africa, Latin America (global south), and the USA, UK, and Australia (global north) consider how the capability approach can contribute as a practical framework to achieving the SDGs' ambitions for social, economic, political, and legal progress. Drawing on insights from a range of disciplines, this book will be of interest to researchers and practitioners from law, politics, international relations, criminology, international development, sociology, public policy, area studies and others"--
Keywords: Sustainable development; Capabilities approach (Social sciences); BUSINESS & ECONOMICS / Development / Sustainable Development; POLITICAL SCIENCE / NGOs (Non-Governmental Organizations); POLITICAL SCIENCE / Public Policy / Environmental Policy